An Integrative Review of Factors Associated with Patient Attrition from Community Health Worker Programs that Support Diabetes Self-Care. Issue 4 (2nd October 2017) - Merius, Heidy N.; Rohan, Annie J.
ABSTRACT: An integrative review was conducted using PubMed and CINAHL databases to answer: What is known about adult attrition from community health worker (CHW) programs on diabetes self-care? The 14 articles described patients of multiple races who were mainly of lower socioeconomic status. CHW interventions were given in individual meetings and/or group sessions. Incentives to reduce attrition came in different forms. Barriers involved transportation, family obligations, and scheduling conflicts. Attrition from these programs is a multifactorial problem. Alleviating transportation barrier appears to be protective. Program planners should consider these barriers when planning CHW programs.